Case Series: Cryotherapy versus Cold Coagulation as Cervical Pre-Cancer Lesion Treatment - Laila Nuranna; Nessyah Fatahan; Alfu Laily (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: Elaborating the results and comparison of cryotherapy and cold coagulation for cervical pre-cancer lesion cases in West Cakung Primary Health Center, Jakarta, Indonesia. Methods: Observation were conducted from cervical pre-cancer lesion cases which was found by visual inspection with acetic acid (VIA) method. Those cases were directed into cryotherapy or cold coagulation based on randomization sampling. After 6-months post therapy, the lesions were assessed. This study was administered on Cakung Barat Health Center, Jakarta, Indonesia on April-December 2018. Of 10 cases, 5 were treated using cryotherapy and the rest with cold coagulation. Result: After 6 months follow up, 1 of 5 patients from each therapies still has VIA positive result. The side effect in form of spotting after 1 month of cryotherapy and cold coagulation were 1/5 and 3/5, respectively. There were no other side effects reported during the 6-months follow up for both treatments. Conclusion: The result of both treatments are relatively same in converting VIA positive into negative, proved with each therapies have turned 4 for 5 patients with prior VIA positive into negative. The side effects endured by respondents were minimal in 1 month post therapy, while there were no significant side effects after 6 months post therapy. Kata Kunci : cervix, cold coagulation, cryotherapy, pre cancer lesion.